Comparing usage between dynamic and static e-reference collections. Issue 3 (6th July 2015) - Lamothe, Alain R
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article was to present the results of a quantitative analysis that compared usage levels between an e-reference collection that has experienced continual updated content and growth and an e-reference collection that has not experienced any recent changes. The aim of the study was to determine quantitatively if e-reference collections with dynamic content experience greater levels of usage compared to e-reference collections that are static in both size and content. Design/methodology/approach – E-reference data were separated into a dynamic collection and a static collection. Usage for e-reference belonging to the dynamic collection was compared to usage of e-reference belonging to the static collection. The number of e-reference was obtained by simple count. Additional statistics tracked include the number of viewings. A linear regression analysis was used to determine the strength of the linear relationship between collection size and usage. Findings – Results indicate that e-reference collections that continue to grow in both size and content also continue to experience year-to-year increases in usage. E-reference collections that remain static in size and content experienced a decline in usage. A linear regression analysis indicates the existence of an extremely strong linear relationship between dynamic content and usage. A weaker linear relationship was calculated for static content. Originality/value – To this author's knowledge, this research is the first to systematically and quantitatively compare usage levels between e-reference titles from growing collections to collections that have not had any new titles added recently.